1985
DOI: 10.1055/s-2007-1017361
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Features and Physiological Properties of Central Serotonin Neurons

Abstract: The authors describe the anatomical features and physiological properties of central serotonergic neurons. The central serotonin neurons (part of which store peptides [substance P, TRF, enkephalins] in addition to 5HT) are highly collateralized reticular-type brain stem neurons receiving multi-modal afferent information from ascending sensory and descending motor pathways. They are under control by noradrenergic, peptidergic and and gaba-ergic projection neurons and interneurons. Furthermore, they establish va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…However, given the multiplicity of serotonin receptors that could mediate the glucose metabolic response to fenfluramine, as well as the possibility raised by studies of serotonin metabolites that pre-synaptic availability may be reduced in impulsive-aggressive patients, further studies will be required to identify the specific serotonergic components altered in impulsive-aggressive patients. Furthermore, serotonergic neurons may have downstream effects on other brain neurotransmitter systems, for example, by activating inhibitory GABAminergic interneurons or even by modulating subcortical dopamine receptor sensitivity (Baumgarten and Lachenmayer 1985). These downstream effects are unlikely to account, however, for the proximal effects of fenfluramine on orbital frontal and cingulate cortex observed in this study.…”
Section: Discussionmentioning
confidence: 72%
“…However, given the multiplicity of serotonin receptors that could mediate the glucose metabolic response to fenfluramine, as well as the possibility raised by studies of serotonin metabolites that pre-synaptic availability may be reduced in impulsive-aggressive patients, further studies will be required to identify the specific serotonergic components altered in impulsive-aggressive patients. Furthermore, serotonergic neurons may have downstream effects on other brain neurotransmitter systems, for example, by activating inhibitory GABAminergic interneurons or even by modulating subcortical dopamine receptor sensitivity (Baumgarten and Lachenmayer 1985). These downstream effects are unlikely to account, however, for the proximal effects of fenfluramine on orbital frontal and cingulate cortex observed in this study.…”
Section: Discussionmentioning
confidence: 72%
“…1 and 2). A species difference between cats and rats with regard to 5-HT dependence of sleep control has been suggested (Baumgarten and Lachenmayer, 1985). There are no known species difference in metabolism or uptake inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…We also wanted to confirm the REM sleep suppressant action in cats. A species difference between cats and rats with regard to 5-HT dependence of sleep control has been suggested (Baumgarten and Lachenmayer, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It is of note that 5-HT has been found to function as an inhibitory neurotransmitter in the optic nerve (Gawel et al,198l), optic radiation, and occipital lobes (Baumgarten & Lachenmayer, 1985). Moreover, Holder et al (1980) found a significant correlation between CSF 5-HIAA levels and VEP latency in patients undergoing surgery and Harrer and Fischbach (1973) and Kisser and Harrer (1974) reported that administration of the 5-HT precursor tryptophan in conjunction with tyrosine and L-dopa effectively abolished the negative effect of artificial overheating on the flicker-fusion threshold in MS patients.…”
Section: Lead-demyelination As An Epiphenomenon In Multiple Sclerosismentioning
confidence: 99%